Analysis of educational services for kindergarten and the efficiency of its distribution in the sectors of the city of Hilla using the Geographic Information Systems GIS - Hussain drewel, Hanan (Journal of College of Education, 2021)
Represents the services one important indicators that reflect the evolution of society and the population level it, study aimed mainly to study the efficiency of the distribution services of (kindergartens) in the city of Hilla. Has also been conducting a comprehensive survey of all Ryadh, in order to provide a database on sites such services , in addition to data on numbers of students and teachers. The study used the descriptive and analytical (mathematical and statistical), through the use of software (SPSS), and the program (Excel) and analysis of date collected through field work, as I took this study trend applied to modern techniques of using geographic information systems (Gis), to build a base spatial information, and analysis of spatial patterns and raster closest neighbor, which enables through , for the most specific criteria for efficient distribution of these services and the extent of its commitment to the terms of the best location ،The study indicated the presence of random distribution of kindergartens in the city of Hilla, because not to the prior planning, standards should not be applied the planning as well as the study pointed to the weakness of the efficiency and effectiveness of these services.